2002
DOI: 10.1124/dmd.30.12.1484
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nicotine and CotinineN-Glucuronidations in Human Liver Microsomes

Abstract: ABSTRACT:The nicotine and cotinine N-glucuronidations in human liver microsomes were characterized. The Eadie-Hofstee plots of nicotine N-glucuronidation in human liver microsomes were clearly biphasic, indicating the involvement of multiple enzymes. The apparent K m and V max values were 33.1 ؎ 28.1 M and 60.0 ؎ 21.0 pmol/ min/mg and 284.7 ؎ 122.0 M and 124.0 ؎ 44.0 pmol/min/mg for the high-and low-affinity components, respectively, in human liver microsomes (n ‫؍‬ 4). However, the Eadie-Hofstee plots of coti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 29 publications
5
62
1
Order By: Relevance
“…The reasons for this are unclear, although 89-fold variability in the rates of nicotine N-glucuronidation has been observed in a panel of microsomes from 14 livers (Nakajima and Yokoi, 2005). The commercially sourced HLM employed in this study were a pool from 150 donors (equal numbers of males and females), whereas most reports have generally used microsomes from fewer donors (Ghosheh and Hawes, 2002;Nakajima et al, 2002;Kaivosaari et al, 2007). Similarly, previous studies with UGT2B10 have used different expression systems to the Supersomes used in this work.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The reasons for this are unclear, although 89-fold variability in the rates of nicotine N-glucuronidation has been observed in a panel of microsomes from 14 livers (Nakajima and Yokoi, 2005). The commercially sourced HLM employed in this study were a pool from 150 donors (equal numbers of males and females), whereas most reports have generally used microsomes from fewer donors (Ghosheh and Hawes, 2002;Nakajima et al, 2002;Kaivosaari et al, 2007). Similarly, previous studies with UGT2B10 have used different expression systems to the Supersomes used in this work.…”
Section: Discussionmentioning
confidence: 65%
“…Previously reported K m and V max values for cotinine N-glucuronidation by HLM range from 0.93 to 5.43 mM and 643 to 696 pmol/min.mg, respectively (Ghosheh and Hawes, 2002;Nakajima et al, 2002;Chen et al, 2007;Kaivosaari et al, 2007), whereas K m values of 0.47 and 1.0 mM have been reported for cotinine N-glucuronidation by recombinant UGT2B10 (Chen et al, 2007;Kaivosaari et al, 2007). The mean K m (2.78 mM) and V max (297 pmol/mg.min) values for human liver microsomal cotinine N-glucuronidation determined in this study tended to be higher and lower, respectively, than previously reported values.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the highly signiˆcant correlation between the nicotine N-glucuronidation and cotinine N-glucuronidation in human liver microsomes, the same UDPglucuronosyltransferase (UGT) isoform(s) might be involved in these glucuronidations. We clariˆed that nicotine and cotinine N-glucuronidation are catalyzed mainly by UGT1A4 and partly by UGT1A9 with inhibition analyses and correlation analyses, 44) which were subsequently supported in a report by Kuehl and Murphy. 45) Large interindividual variability in the nicotine Nglucuronidation (¿22 fold) and cotinine N-glucuronidation (¿89 fold) in human liver microsomes was observed (Fig.…”
Section: Nicotine and Cotinine N-glucuronidationsmentioning
confidence: 62%
“…Variation among racial groups also exists in other nicotine metabolic pathways such as nicotine and cotinine glucuronidation (Benowitz et al, 1999). This suggests that additional differences in the rates of nicotine metabolism among racial groups may be due to variation in the frequencies of allelic variants in genes responsible for nicotine-N-1-oxidation (i.e., flavin containing monooxygenase 3 gene; Cashman et al, 1995) and glucuronidation (i.e., UDP-glucuronyltransferase genes; de Leon, 2003;Nakajima et al, 2002). For these reasons, we plan to pursue a twin study of nicotine metabolism in other racial populations in the near future (e.g., Yang et al, 2002).…”
Section: Lack Of Ethnic Variationmentioning
confidence: 99%